DEEP SUBMARINE PYROCLASTIC ERUPTIONS: THEORY AND PREDICTED LANDFORMS AND DEPOSITS - Head J.W.; Wilson L. (My University, 2003)
Submarine pyroclastic eruptions at depths greater than a few hundred meters are generally considered to be rare or absent because the pressure of the overlying water column is sufficient to suppress juvenile gas exsolution so that magmatic disruption and pyroclastic activity do not occur. Consideration of detailed models of the ascent and eruption of magma in a range of sea floor environments shows, however, that significant pyroclastic activity can occur even at depths in excess of 3000 m. In order to document and illustrate the full range of submarine eruption styles, we model several possible scenarios for the ascent and eruption of magma feeding submarine eruptions: (1) no gas exsolution; (2) gas exsolution but no magma disruption; (3) gas exsolution, magma disruption, and hawaiian-style fountaining; (4) volatile content builds up in the magma reservoir leading to hawaiian eruptions resulting from foam collapse; (5) magma volatile content insufficient to cause fragmentation normally but low rise speed results in strombolian activity; and (6) volatile content builds up in the top of a dike leading to vulcanian eruptions. We also examine the role of bulk-interaction steam explosivity and contact-surface steam explosivity as processes contributing to volcaniclastic formation in these environments. We concur with most earlier workers that for magma compositions typical of spreading centers and their vicinities, the most likely circumstance is the quiet effusion of magma with minor gas exsolution, and the production of somewhat vesicular pillow lavas or sheet flows, depending on effusion rate. The amounts by which magma would overshoot the vent in these types of eruptions would be insufficient to cause any magma disruption. The most likely mechanism of production of pyroclastic deposits in this environment is strombolian activity, due to the localized concentration of volatiles in magma that has a low rise rate; magmatic gas collects by bubble coalescence, and ascends in large isolated bubbles which disrupt the magma surface in the vent, producing localized blocks, bombs, and pyroclastic deposits. Another possible mode of occurrence of pyroclastic deposits results from vulcanian eruptions; these deposits, being characterized by the dominance of angular blocks of country rocks deposited in the vicinity of a crater, should be easily distinguishable from strombolian and hawaiian eruptions. However, we stress that a special case of the hawaiian eruption style is likely to occur in the submarine environment if magmatic gas buildup occurs in a magma reservoir by the upward drift of gas bubbles. In this case, a layer of foam will build up at the top of the reservoir in a sufficient concentration to exceed the volatile content necessary for disruption and hawaiian-style activity; the deposits and landforms are predicted to be somewhat different from those of a typical primary magmatic volatile-induced hawaiian eruption. Specifically, typical pyroclast sizes might be smaller; fountain heights may exceed those expected for the purely magmatic hawaiian case; cooling of descending pyroclasts would be more efficient, leading to different types of proximal deposits; and runout distances for density flows would be greater, potentially leading to submarine pyroclastic deposits surrounding vents out to distances of tens of meters to a kilometer. In addition, flows emerging after the evacuation of the foam layer would tend to be very depleted in volatiles, and thus extremely poor in vesicles relative to typical flows associated with hawaiian-style eruptions in the primary magmatic gas case. We examine several cases of reported submarine volcaniclastic deposits found at depths as great as ~3000 m and conclude that submarine hawaiian and strombolian eruptions are much more common than previously suspected at mid-ocean ridges. Furthermore, the latter stages of development of volcanic edifices (seamounts) formed in submarine environments are excellent candidates for a wide range of submarine pyroclastic activity due not just to the effects of decreasing water depth, but also to: (1) the presence of a summit magma reservoir, which favors the buildup of magmatic foams (enhancing hawaiian-style activity) and episodic dike emplacement (which favors strombolian-style eruptions); and (2) the common occurrence of alkalic basalts, the CO2 contents of which favor submarine explosive eruptions at depths greater than tholeiitic basalts. These models and predictions can be tested with future sampling and analysis programs and we provide a checklist of key observations to help distinguish among the eruption styles.
Keywords: SUBMARINE; BASALT; ERUPTIONS; VOLCANICLASTIC; PYROCLASTIC; HYALOCLASTITE; HAWAIIAN; STROMBOLIAN